Carbon nanoscrolls by pyrolysis of a polymer - Yadav, Prasad; Warule, Sambhaji; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2012)
3D network of carbon nanoscrolls was synthesized starting from pyrolysis of poly(acrylic acid-co-maleic acid) sodium salt. It is a catalyst-free process where pyrolysis of polymer leads to formation of carbon form and sodium carbonate. Upon water soaking of pyrolysis product, the carbon form undergoes self-assembly to form carbon nanoscrolls. The interlayer distance between the walls of carbon nanoscroll was found to be 0.34 nm and the carbon nanoscrolls exhibited a surface area of 188 m(2)/g as measured by the BET method. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon nanoscrolls; Polymer; Pyrolysis; supercapacitor